Oxidation of Some 1-Aryl Ethanols Using Permanganate in Aqueous Acetic Acid Medium: A Kinetic Study - RAJENDRAN, P.; ABDU RAHIMAN, K.K.; RADHAKRISHNAN NAIR, T.D. (Asian Journal of Chemistry, 2010)
Kinetic studies on the permanganate oxidation of some 1-aryl carbinols in aqueous acetic medium have been carried out. The reaction showed first order dependence with respect to both the oxidant and the substrate concentration. The rate increased with increase in the [H+] but with a complex order. Effects of ionic strength and dielectric constant of the medium have been investigated. The effects of the various substituents at the para position of the benzene ring gave quite interesting results and were not in conformity with the Hammett equation. Both the electron-releasing' and the electron-withdrawing groups have been found to enhance the rate. A plausible mechanism guided by frontier molecular orbital theory was suggested.